Next-Generation Sequencing-Aided Rapid Molecular Diagnosis of Occult Macular Dystrophy in a Chinese Family - Qi, Yu-He; Gao, Feng-Juan; Hu, Fang-Yuan; Zhang, Sheng-Hai; Chen, Jun-Yi; Huang, Wan-Jing; Tian, Guo-Hong; Wang, Min; Gan, De-Kang; Wu, Ji-Hong; Xu, Ge-Zhi (Frontiers in Genetics, 2017)
Purpose: To show early, rapid and accurate molecular diagnosis of occult macular dystrophy (OMD) in a four-generation Chinese family with inherited macular dystrophy. Methods: In the current study, we comprehensively screened 130 genes involved in common inherited nonsyndromic eye diseases with next-generation sequencing (NGS)-based target capture sequencing of the proband of a four-generation Chinese family that has suffered from maculopathy without a definitive diagnosis for over ten years. Variants were filtered and analyzed to identify possible disease-causing variants before validation by Sanger sequencing. Results: Two heterozygous mutations—RP1L1 c.133 C>T (p.Arg45Trp), which is a hot spot for  OMD, and ABCA4 c.6119 G>A (p.Arg2040Gln), which was identified in Stargardt’s disease (SD) were found in three patients, but neither of the mutations was found in the unaffected individuals in the same family, who are phenotypically normal or in the normal control volunteers. Conclusion: These results can not only confirm the diagnosis of OMD in the proband, but also provide presymptomatic diagnosis of the proband’s children before the onset of visual acuity impairment and guidance regarding the prognosis and management of these patients. Heterozygous mutations of RP1L1 c.133 C>T (p.Arg45Trp) and ABCA4 c.6119 G>A (p.Arg2040Gln) are likely responsible for OMD. Our results further extend our current understanding of the genetic basis of OMD, and emphasize the importance of molecular diagnosis and genetic counselling for OMD.